The 2012 Olympic Ambassadors and sustainable tourism legacy - Nichols, G.; Ralston, R.; Holmes, Kirsten (Routledge, 2017)
This paper examines the capacity of the London (2012) Olympic Ambassador volunteer programmes to create a sustainable tourism legacy. It contributes to the literature on event legacies, particularly the role of volunteers promoting tourism in their home destination. Using an exploratory inductive approach, semi-structured in-depth interviews were conducted, in 2012 and 2013, with managers of all 11 Ambassador volunteer programmes associated with London and the 10 other regional venues that hosted London Olympic and Paralympic Games events. These show that volunteer Ambassadors enhanced tourist experiences during the Games through the Ambassadors’ pride in their home city, enthusiasm and local knowledge. However, although the Ambassador programmes had aspirations to create a sustainable legacy, in the form of a pool of experienced volunteers to support future events and further tourist visits, this was severely constrained by cuts in local government budgets. The Government Olympic Executive provided a coordinating role leading up to the Games, but neither they nor the London Organising Committee for the Olympic Games provided practical assistance for legacy development. This was a missed opportunity to channel the enthusiasm of mega-event volunteers into further volunteering to promote tourism.